Electronic Administration Styles and Their Determinants. Evidence from Spanish Local Governments - José Valeriano FRÍAS-ACEITUNO; Isabel María GARCÍA-SÁNCHEZ; Luis RODRÍGUEZ-DOMÍNGUEZ (Transylvanian Review of Administrative Sciences, 2014)
This paper analyzes the factors underlying the development of e-government, as an overall process, as well as of each of the three stages identified in the prior literature (e-government, egovernance and e-democracy). The analysis has focused on 102 Spanish municipalities, and it consists in a content analysis of their web pages, based on an information index, in order to develop a dependency model. The results obtained indicate that Spanish municipalities show high information transparency regarding economic, environmental and social matters, allowing the undertaking of administrative proceedings online and actively promoting the participation of interest groups in strategic, sustainable and managerial issues. Our findings stress the importance of the municipality’s size and the ruling party’s political ideology of a deeper commitment with the development of e-government.